Assessment of antibiotic use among residents of Paco, Manila - Badong, Karla Joyce S.
Several studies were done worldwide regarding antimicrobial resistance which pointed antibiotic use as its leading cause. In the Philippine however, limited published studies regarding the use of antibiotics exist. This study assessed the antibiotics use of Paco, Manila residents. Variables such as demographic factors, antibiotic use, knowledge about antibiotic use, sources of information, and awareness about antimicrobial resistance were identified and described. Relationship of demographic factors with antibiotic use and knowledge about antibiotic use were also explored. A self- administered questionnaire was distributed among the residents of the different barangay of Paco, Manila. Results of the study showed that the most commonly used antibiotic was amoxicillin and antibiotics were commonly used for upper respiratory infections. The most common dosage form of antibiotics they used was capsule and drugstores were the common source of antibiotics. Most of the respondents took antibiotics after meals, with water, and until the time/regimen instructed by the prescriber. Also, most of them brought all the medicines prescribed to them. The respondents usually stop taking the drug and consult their doctor when they think that the antibiotic drug they were taking was not effective and/or when they experience undesirable effects from it. Excess antibiotics were usually kept and used again when illness/condition returns or thrown away to the waste bin. Furthermore, majority take antibiotics to present illness do not base their antibiotic use on their own decision, and encourage their relatives to take antibiotics. Although majority of the respondents are well aware of antimicrobial resistance, a lot of them had wrong knowledge about the indications and risk of antibiotics which may contribute to antimicrobial resistance. This necessitates the need of pharmacists to be more proactive in the provision of medicine information.